The new Jewish table : modern seasonal recipes for traditional dishes - Gray, Todd (St. Martin's Press, 2013)
"The New Jewish Table explores the melding of two different cooking cultures, seasonal American and Eastern-European Jewish, sharing the mouth-watering recipes that result from this flavorful union from authors, chef Todd Gray and his wife Ellen Kassoff Gray. More than a love story about what one can do with fresh ingredients, Todd and Ellen talk about the food they grew up with, their life together, and how rewarding the sharing of two people's traditions--and meals--can be. When Chef Todd married his wife, Ellen, who is Jewish, their union brought about his initiation into the world of Jewish cooking. In 1999, Todd combined his love for farm-to-table ingredients with his passion for Jewish cuisine, opening the acclaimed Equinox Restaurant in Washington, D.C. With more than 125 recipes including reinterpretations of traditional Jewish favorites made with fresh, seasonal ingredients, from Yukon Gold and Sweet Potato Latkes, Ellen's Falafel with Pickled Vegetables and Minted Lemon Yogurt, and Roasted Heirloom Beets with Capers and Pistachios, to Matzo-Stuffed Cornish Game Hens, Fig and Port Wine Blintzes, and Chocolate Hazelnut Rugelach, there are recipes for every occasion that the entire family will enjoy"--